Socio-economic impacts of community based forest enterprises in mid hills of Nepal-Case Study from Dolakha district - Acharya, R.P. (Banko Janakari, 2007)
This paper endeavors to assess the socio-economic impact of FUG members affiliated with three Community Based Forest Enterprises (CBFEs) in Dolakha district. Important socio-economic variables, especially household income, gender and equity, decision making process, benefit sharing and resource management were analyzed. The study concludes that the CBFEs have created a positive impact on the socio-economic aspects of rural populace. Key words: Community based forest enterprises, Gender and equity, Benefit sharing, Decision making, Resource management Banko Janakari Vol.15(2) 2005 pp43-47